Pomegranate Pomace Extract with Antioxidant, Anticancer, Antimicrobial, and Antiviral Activity Enhances the Quality of Strawberry-Yogurt Smoothie - Nouf H. Alsubhi; Diana A. Al-Quwaie; Ghadeer I. Alrefaei; Mona Alharbi; Najat Binothman; Majidah Aljadani; Safa H. Qahl; Fatima A. Jaber; Mashael Huwaikem; Huda M. Sheikh; Jehan Alrahimi; Ahmed N. Abd Elhafez; et al. (Bioengineering, 2022)
Valorizing the wastes of the food industry sector as additives in foods and beverages enhances human health and preserves the environment. In this study, pomegranate pomace (PP) was obtained from the company Schweppes and exposed to the production of polyphenols and fiber-enriched fractions, which were subsequently included in a strawberry-yogurt smoothie (SYS). The PP is rich in carbohydrates and fibers and has high water-absorption capacity (WAC) and oil-absorption capacity (OAC) values. The LC/MS phenolic profile of the PP extract indicated that punicalagin (199 g/L) was the main compound, followed by granatin B (60 g/L) and pedunculagin A (52 g/L). Because of the high phenolic content of PP extract, it (p ≤ 0.05) has high antioxidant activity with SC50 of 200 µg/mL, besides scavenging 95% of DPPH radicals compared to ascorbic acid (92%); consequently, it reduced lung cancer cell lines’ viability to 86%, and increased caspase-3 activity. Additionally, it inhibited the growth of pathogenic bacteria and fungi i.e., L. monocytogenes, P. aeruginosa, K. pneumonia, A. niger, and C. glabrata, in the 45–160 µg/mL concentration range while killing the tested isolates with 80–290 µg/mL concentrations. These isolates were selected based on the microbial count of spoiled smoothie samples and were identified at the gene level by 16S rRNA gene sequence analysis. The interaction between Spike and ACE2 was inhibited by 75.6%. The PP extract at four levels (0.4, 0.8, 1.2, and 1.4 mg/mL) was added to strawberry-yogurt smoothie formulations. During 2 months storage at 4 °C, the pH values, vitamin C, and total sugars of all SYS decreased. However, the decreases were gradually mitigated in PP-SYS because of the high phenolic content in the PP extract compared to the control. The PP-SYS3 and PP-SYS4 scored higher in flavor, color, and texture than in other samples. In contrast, acidity, fat, and total soluble solids (TSS) increased at the end of the storage period. High fat and TSS content are observed in PP-SYS because of the high fiber content in PP. The PP extract (1.2 and 1.6 mg/mL) decreases the color differences and reduces harmful microbes in PP-SYS compared to the control. Using pomegranate pomace as a source of polyphenols and fiber in functional foods enhances SYS’s physiochemical and sensory qualities.